Comparative Effect of Gamma Irradiation, UV-C and Hot Water on Antioxidant Potential of Mango (Mangifera indica L.) Fruit - Chatha, Zia Ahmad; Ahmad, Asif; Zahoor, Tahir; Raza, Ali (Pakistan Journal of Nutrition, 2013)
Use of gamma irradiation and UV-C was compared over conventional used hot water treatment on mango pulp and peel. The storage study was also carried out to explore the potential of these techniques for the retention of total polyphenolic substances and antioxidants activity. Results indicated that polyphenolic substances decreased during storage. This decline in polyphenolic substances can be controlled by using gamma irradiation and UV-C treatment in mango peel and pulp. Lower doses (0.5 KGY) is more effective in controlling these losses. Comparing the varietal differences, white chaunsa showed better phenolic and antioxidant retention potential as compared to black chaunsa.